2016
DOI: 10.1097/mnm.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of survival, safety, and efficacy after transarterial chemoembolization and radioembolization of Barcelona Clinic Liver Cancer stage B-C hepatocellular cancer patients

Abstract: Although chemoembolization and radioembolization for BCLC Stage B-C patients have similar levels of safety and efficacy, they differ in OS. In this retrospective study, patients undergoing radioembolization had a longer survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…Studies were excluded due to insufficient data and information ( n =2), cTACE combined with TARE (90Y) ( n =4), treatment either cTACE or TARE (90Y; n =2), DEB-TACE as treatment ( n =3), and non-clinical studies ( n =15). Finally, 11 articles met the inclusion criteria for our meta-analysis 13-23 . …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were excluded due to insufficient data and information ( n =2), cTACE combined with TARE (90Y) ( n =4), treatment either cTACE or TARE (90Y; n =2), DEB-TACE as treatment ( n =3), and non-clinical studies ( n =15). Finally, 11 articles met the inclusion criteria for our meta-analysis 13-23 . …”
Section: Resultsmentioning
confidence: 99%
“…All of the articles were published between 2009 and 2016 and included with nine observational studies 13,16-23 and two RCTs 14,15 . The locations of the studies included Germany, Spain, China, Egypt, Turkey, and the USA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the radioembolization procedure, microspheres bonded with a radioisotope (yttrium-90 [Y-90]) are infused into the arteries that supply the tumor. 15,23 Retrospective reviews have reported comparable or improved OS with TARE versus TACE, [24][25][26] and a randomized trial reported a significantly longer median time to progression after TARE (>26 vs 6.8 months) but no difference in OS. 19 On the basis of liver explant pathology after radioembolization and subsequent transplantation, 61% of treated lesions (and 89% of lesions <3 cm) exhibited complete pathologic necrosis.…”
Section: Radioembolizationmentioning
confidence: 99%